Holocene wildfire regimes in forested peatlands in western Siberia: interaction between peatland moisture conditions and the composition of plant functional types - Feurdean, Angelica; Diaconu, Andrei-Cosmin; Pfeiffer, Mirjam; Gałka, Mariusz; Hutchinson, Simon M.; Butiseaca, Geanina; Gorina, Natalia; Tonkov, Spassimir; Niamir, Aidin; Tantau, Ioan; Kirpotin, Sergey (2021)
Wildfire is the most common disturbance type in boreal forests and can trigger significant changes in forest composition. Waterlogging in peatlands determines the degree of tree cover and the depth of the burning horizon associated with wildfires. However, interactions between peatland moisture, vegetation composition and flammability, and fire regime in forested peatland in Eurasia remain largely unexplored, despite their huge extent in boreal regions. To address this knowledge gap, we reconstructed the Holocene fire regime, vegetation composition, and peatland hydrology at two sites in Western Siberia near Tomsk Oblast, Russia. The palaeoecological records originate from forested peatland areas in predominantly light taiga ( Pinus-Betula ) with the increase in dark taiga communities ( Pinus sibirica , Picea obovata , Abies sibirica ) towards the east. We found that the past water level fluctuated between 8 and 30 cm below the peat surface. Wet peatland conditions promoted broadleaf trees ( Betula ), whereas dry peatland conditions favoured conifers and a greater forest density (dark-to-light-taiga ratio). The frequency and severity of fire increased with a declining water table that enhanced fuel dryness and flammability and at an intermediate forest density. We found that the probability of intensification in fire severity increased when the water level declined below 20 cm suggesting a tipping point in peatland hydrology at which wildfire regime intensifies. On a Holocene scale, we found two scenarios of moisture-vegetation-fire interactions. In the first, severe fires were recorded between 7.5 and 4.5 ka BP with lower water levels and an increased proportion of dark taiga and fire avoiders ( Pinus sibirica at Rybanya and Abies sibirica at Ulukh Chayakh) mixed into the dominantly light taiga and fire-resister community of Pinus sylvestris . The second occurred over the last 1.5 ka and was associated with fluctuating water tables, a declining abundance of fire avoiders, and an expansion of fire invaders ( Betula ). These findings suggest that frequent high-severity fires can lead to compositional and structural changes in forests when trees fail to reach reproductive maturity between fire events or where extensive forest gaps limit seed dispersal. This study also shows prolonged periods of synchronous fire activity across the sites, particularly during the early to mid-Holocene, suggesting a regional imprint of centennial to millennial-scale Holocene climate variability on wildfire activity. Increasing human presence in the region of the Ulukh-Chayakh Mire near Teguldet over the last four centuries drastically enhanced ignitions compared to natural background levels. Frequent warm and dry spells predicted for the future in Siberia by climate change scenarios will enhance peatland drying and may convey a competitive advantage to conifer taxa. However, dry conditions, particularly a water table decline below the threshold of 20 cm, will probably exacerbate the frequency and severity of wildfire, disrupt conifers’ successional pathway and accelerate shifts towards more fire-adapted broadleaf tree cover. Furthermore, climate-disturbance-fire feedbacks will accelerate changes in the carbon balance of forested boreal peatlands and affect their overall future resilience to climate change.